DINAMIKA PELAKSANAAN KAWASAN PERDAGANGAN BEBAS DAN PELABUHAN BEBAS (FREE TRADE ZONE) BATAM - Nofri Yanti; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Free Trade Zone and Free Port of Batam regulated in Law No. 46 of 2007.Region free trade and free port of Batam This provides convenience to theinvestors to invest in Batam customs fee exempt investors to export or importactivities. The existence of strategic. Batam city makes more and more in comingto the investors. The arrival of investors in Batam certainly bring a change in thecity of Batam both in terms of physical and non-physical development. With thepolicy of free trade zone and free port of Batam certainly provide a lot of jobs tothe community and to improve economic growth, as well as the determination ofthe Batam Free Trade Zone and Free Port Batam also resulted in dependence onother countriesKeywords: Free Trade Zone and economic gro